Tinjauan Prinsip-Prinsip Ekonomi Islam dalam Praktik Memasarkan Ikan Asin (Studi Kasus di Desa Lambur Luar Kecamatan Muara Sabak Timur) - Wandi, Wandi; Musthofa, M Arif; Ningsih, Ratnah (JES (Jurnal Ekonomi Syariah), 2020)
This research is motivated by the writer’s anxiety regarding the Review of Islamic Economic Principles in Marketing of Salted Fish (Case Study in Lambur Luar Village, Muara Sabak Timur District). The purpose of this research is how are the factors that hinder the marketing of Salted Fish in Lambur Luar Village. What are the obstacles marketing Salted Fish in Lambur Luar Village. In general, the result is from the analysts, the practice of buying and selling salted fish in Lambur Luar village where a seller sells salted fish which is still wet and has damaged fish is also not in accordance with the initial words.Â There are those who consider it a normal thing, but there are also those who feel disadvantaged.Â Those who think it is normal are justified because their goal is for the buyer to eat and be delicious or satisfied. The view of Islamic law on the practice of buying and selling salted fish in Lambur Luar village has two legal conclusions.Â Namely: first, the law is permissible because the buyer and seller have a willing heart, while the second is haram because in the heart, there is no willingness from the buyer of the salted fish Â Keywords: practice; marketing; salted fish